PERILAKU KONSUMEN DALAM PERILAKU PEMBELIAN SUSU KEMASAN : STUDI EKSPLORATIF - Imam Nuraryo (Jurnal Manajemen, 2017)
Milk is one of the many products in the consumption by the public. This research purposes to know consumer behavior in North Jakarta in purchasing tetrapacked milk. The Data collection was conducted with distributing questionnaires.the sampling technique used in this research was accidental sampling. The number of respondents was 76 people. The result indicated that the determinants of consumers in purchasing dairy products is based on the taste then followed by a brand that has been known by the public.Keywords:.Consumer Behavior, Purchasing Behavior, Explorative Study